Synthesis and Local Electronic Structure of Calcite Nanoparticles - Singh, Jitendra Pal; Lim, Weon Cheol; Won, Sung Ok; Kim, Sang Ok; Chae, Keun Hwa (AMER SCIENTIFIC PUBLISHERS, 2016)
Calcite nanoparticles were synthesized using modified sol-gel method starting from calcium nitrate. Annealing of precursor at 0, 300, and 400 degrees C leads to the formation of amorphous phase of calcium carbonate. At 500 degrees C, amorphous phase converted into calcite phase of calcium carbonate, which retains at 600 degrees C. At higher temperature, mixed phases of calcium hydroxide and calcium oxide appear along with the calcite phase. Calcite nanoparticles synthesized at 500 and 600 degrees C exhibit particle size of 23 and 43 nm, respectively. X-ray absorption spectroscopy measurements performed on these materials show that electronic structure is sensitive to crystalline and amorphous calcite phase, however it is almost insensitive to mixed calcite phases present in the mixture of CaO and Ca(OH)(2). Moreover, C K-edge spectra infer about the attached water molecules with calcite.
Keywords: CARBONATE; GROWTH; XANES; WATER; MORPHOLOGY; REMOVAL; SPECTRA; ACID; EDGE